Análise do discurso midiativista: uma abordagem às transmissões simultanêas do Midia Ninja - Antônio Augusto Braighi Andrade (2016)
In Brazil 2011, one of the first citizenship initiatives of online and real time protests registration appeared. This was the embryo which would become one of the most discussed media activism articulations in the country. This would effectively only happen two years later, when the nation had to deal with many manifestations, leading thousands of people to Brazilian cities streets, in a movement known as 2013 June Journeys. These acts were characterized by a crisis scream for representativeness, political and media; therefore, parliamentary flags and corporative media logos were not well accepted in thedemonstrations. It is in this context that Media Ninja gets representativeness, an independent communication collective that closely registered the protests, live, via Internet, marking,inclusively, the traditional communication vehicles. In 2014, during the Soccer World Cup, once again the Ninjas were in the streets- period that represents the examined scenario of this research. Facing the emergence of such phenomena, the aim of this paper was to describe and analyze Media Ninja production conditions, trying to understand the place which the collective occupies in the media discursive regime that we have in the contemporaneity. It is important to register that this paper talks, exclusively, about the simultaneous transmissions ofMedia Ninja and not the series of other sallies that it generates. Therefore, as specific intents, we undertook the circumscription of structural aspects that constitute the technical device ofthe vehicle production; the description and analyses of the regular communicational and enunciative collective device; and at last, the examination of the interaction dynamic of the media activist group with their receptors/interlocutors on the Twitcasting platform. As a critical appreciation mechanism, we initiated the Discourse Analysis, more specifically towards the semiolinguistic field looking for contributions that helped in the methodological constitution. The tooling which consists of a three part structure, evaluates the technical, interactional, contextual, verbal-enuncive-enunciative, audiovisual, image-text, and effect dimensions. However, we also settled here in a theoretical ground that helps to reflect historically and conceptually about the occupation of networks and streets by the society, as well as how the media and the mediation mechanisms exert a fundamental role in this scenario. After analyses, the result is a detailed breakdown of the collective, which exposes its main properties and helps in a characterization taken different from that which is propaganda in the common sense, in also presenting a concept about the media activism in a more accurate way. It is believed that the considerations here set do not close the phenomena that is being lived, in full ongoing, suffering and attributing mutations in the web, political, social 12 movements of the media field, among other fronts. However, we leave some assertive that in a way, help to understand a little (or in part) about our society, its interests, its fears, its needs and desires. Finally, it is believed that this thesis also brings a contribution for one to think about in linguistic studies (and Discourse Analysis) in light of the new media and social intervention fronts, since their application to the examined scenario here cultivated seemed very positive.